E-justice at the dawn of the XXI century (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2024)
Technological innovations represent alternatives to address emergency scenarios that may arise in human life. The application of law and practice in the judicial system does not escape this. Therefore, the general purpose of this work was to analyze the importance of digital justice at the dawn of the 21st century. To this end, a documentary study was implemented under a qualitative approach to break down the phenomenon investigated. Thus, it was determined that the concept of digital justice was catalyzed by the COVID 19 crisis and represents a figure that entails challenges and opportunities, which mainly adhere to its interrelationship with the digital divide and the search for a justice that does not necessarily requires in-person assistance regarding its configuration. It was concluded that e-justice has its basis in ensuring the rights of people and it was recommended to maintain its monitoring to observe its effectiveness within the structures of the States.
Keywords: justice; digital innovation; technology